Investigation of Load Capacity of Steel Concrete Composite Columns SRC Reinforced by IPE - Beiranvand, Peyman; Abdollahifar, Matin; Moradpour, Ahmad; Sadeghi, Golmakani Saeideh (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this study, a column with section IPE and different lengths, completely embedded in concrete, is modelled by finite element software ABAQUS. Columns under different biaxial loading were used and graphs of axial force-axial deformation, interaction axial force, and bending moment and column curve were mapped.
Keywords: seel-concrete composite columns; investigation of load; biaxially loads; żelbetowe kolumny kompozytowe; badania obciążenia; obciążenia dwuosiowe